Memorandum of understanding between Universiti Teknologi MARA and Our Lady of Fatima University College of Pharmacy, Philippines / Fakulti Farmasi - Universiti Teknologi MARA, Fakulti Farmasi (Universiti Teknologi MARA (UiTM), 2020)
UiTM and Our Lady of Fatima University College of Pharmacy will endeavour to strengthen, promote and develop educational and research co-operation on the basis of equality and mutual benefit.